A New Oxopiperazin‐Based Peptidomimetic Molecule Inhibits Prostatic Acid Phosphatase Secretion and Induces Prostate Cancer Cell Apoptosis. Issue 15 (26th September 2016) - Zer Aviv, Pinchas; Shubely, Moran; Moskovits, Yoni; Viskind, Olga; Albeck, Amnon; Vertommen, Didier; Ruthstein, Sharon; Shokhen, Michael; Gruzman, Arie
Abstract: Reduced Prostatic acid Phosphatase (PAcP) secretion is associated with inhibition of the proliferation rate of prostate cancer cells. Signal peptidase 1 (SPase 1) is the main protease that cleaves the signal peptide of secretory proteins and allows their secretion. Thus, we hypothesised that inhibition of SPase 1 might lead to an antiproliferative effect in prostate cancer cells. Using homology computer modelling, we created a human SPase 1 model. With this model we designed and synthesised four novel (S)‐3‐(4‐aminobutyl)piperazin‐2‐one‐based peptidomimetics. The in vitro cytotoxic activity of these compounds was evaluated in the Lymph Node Carcinoma of the Prostate (LNCaP) cancer cell line. Indeed, (S)‐(3‐(2‐(4‐(((benzyloxy)carbonyl)amino)butyl)‐4‐(3‐methoxy‐3‐oxopropyl)‐3‐oxopiperazin‐1‐yl)propyl)boronic acid, compound8 ) reduced PAcP secretion, as well as exhibited significant cytotoxic effect in LNAcP cells. As reported in this study, an antiprostate cancer drug development approach, which is based on inhibiting PAcP secretion, is innovative and it might serve as source for developing novel antiprostate cancer drugs. Abstract : We describe how covalent inhibition of prostatic acid phosphatase secretion was used as a target for developing anti‐prostate cancer drug candidate. A peptidomimetic: methyl (S)‐3‐(3‐(4‐(((benzyloxy)carbonyl)amino)butyl)‐2‐oxopiperazin‐1‐yl)propanoate) was constructed as a "spider" with an oxopiperazin core (body) supplied with flexible arms: a warhead and the enzyme recognition groups.